Taxonomic notes on American Heriades Spinola, 1808 and Leioproctus Smith, 1853 (Hymenoptera: Megachilidae, Colletidae) - Gonzalez, Victor H.; Sepúlveda, Paula A.; Griswold, Terry L. (Zootaxa, 2012)
The purpose of this paper is to document the males of Leioproctus rosellae Gonzalez in Gonzalez & Florez, 2011 (Colletidae, Paracolletini) and Heriades tayrona Gonzalez & Griswold, 2011 (Megachilidae, Osmiini), two solitary bee species recently described based on females from the Caribbean coast of Colombia. Leioproctus rosellae is currently known only from the holotype, while H. tayrona is known from a few specimens from the type locality. The discovery of these species in northern Colombia considerably extended the distribution of Leioproctus Smith (sensu Michener, 2007) and Heriades Spinola in the Western Hemisphere. In the Americas, Leioproctus was known from Chile and Argentina to central Peru and northeastern Brazil, while Heriades was known from southern Canada to Panama and the Greater Antilles (Michener 2007). The discovery of H. tayrona also represented the first record of the tribe Osmiini for South America.